2014
DOI: 10.1002/2014ja020190
|View full text |Cite
|
Sign up to set email alerts
|

Bursty magnetic reconnection under slow shock‐generated whistler waves

Abstract: Nonlinear dynamics of magnetic reconnection with an external sub-Alfvenic parallel shear flow is investigated by using two-dimensional compressible Hall MHD simulation. Two pairs of slow shocks in the inflow region are generated by the sub-Alfvenic shear flow in the MHD simulation. With inclusion of Hall effects, it is found that whistler waves are generated in the downstream region of slow shocks. The whistler waves propagating toward the reconnection region drive a large bursty enhancement in magnetic reconn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The whistler waves, in contrast, can affect the electron dynamics inside the EDR and therefore may contribute to the reconnection triggering. In fact, previous numerical simulations [Birn et al, 2001;Drake et al, 2008;Goldman et al, 2014;Ma et al, 2014] and laboratory experiments [Ji et al, 2004] also emphasize the role of whistlers in facilitating reconnection processes. Apart from the whistlerdriven anomalous resistivity, the electron inertia term can also affect magnetic reconnection inside the EDR.…”
Section: Summary and Discussionmentioning
confidence: 90%
“…The whistler waves, in contrast, can affect the electron dynamics inside the EDR and therefore may contribute to the reconnection triggering. In fact, previous numerical simulations [Birn et al, 2001;Drake et al, 2008;Goldman et al, 2014;Ma et al, 2014] and laboratory experiments [Ji et al, 2004] also emphasize the role of whistlers in facilitating reconnection processes. Apart from the whistlerdriven anomalous resistivity, the electron inertia term can also affect magnetic reconnection inside the EDR.…”
Section: Summary and Discussionmentioning
confidence: 90%
“…Star formation (Norman and Heyvaerts, 1985;Marchand et al, 2019;Wurster et al, 2021), solar atmosphere and the solar wind at Earth distance (Galtier and Buchlin, 2007;González-Morales et al, 2019), dynamo action (Mininni et al, 2002(Mininni et al, , 2005Gómez et al, 2010) and the Earth and planetary magnetospheres (Liu et al, 2013;Dorelli et al, 2015;Xie et al, 2015;Tóth et al, 2016), are only some of the frameworks and science cases tackled in the literature employing the Hall-MHD model. Several studies have also shown that the Hall term enhances the rate of magnetic reconnection (Wang et al, 2001;Morales et al, 2005;Ma et al, 2014;Ma et al, 2018), though there is an ongoing discussion on the role of the Hall current in the emergence of magnetic structures (Mininni et al, 2007). In particular, claims are made that the Hall effect may help amplifying the large-scale magnetic field (Mininni et al, 2005) and the emergence of self-organized structures (Numata et al, 2004;Ohsaki, 2006), while some authors argue it helps instead with the generation of small-scale structures and filaments (Rheinhardt and Geppert, 2002;Miura and Araki, 2014;Martin et al, 2013).…”
Section: Hall-mhd Description Of Plasmasmentioning
confidence: 99%
“…In the outflow region or the ideal MHD region, the ejected velocity of the reconnected magnetic flux must be less than the local Alfvén velocity because of the frozen-in condition, which suggests that the Alfvén wave controls the rate of the magnetic reconnection. With the inclusion of the Hall effect in MHD, the whistler wave can be generated [1].…”
Section: Introductionmentioning
confidence: 99%